Adaptive features of two copper-resistant Pseudomonas strains isolated from a French vineyard soil / Chong Teik Min - Chong, Teik Min (2017)
Trace metals are required in many cellular processes in bacteria but could also be tenacious and cause toxicity when present in excess. Vitis vinifera (grapevine) is a non-rotating crop that has been routinely treated with copper sulphate over the years in order to control fungal diseases. Consequently, such anthropogenic accumulation of copper ions in the vineyard soil causes selection that favours the prevalence of copper resistant microorganisms. Thus it would be of interest to investigate the microbiota inhabiting these soils. DNA methylation is one of the common epigenetic markers found widespread in prokaryotes and often regulates gene expressions under the influence of external factors. Hence, exploring the genetic determinants for metal resistance as well as the methylation patterns could also provide insights on adaptability of these soil inhabitants in the presence of metal induced stress. A bacterial isolation attempt on a French vineyard soil sample has resulted in identification of Pseudomonas strains, shown to confer resistance to copper ions. Phenotypic microarray analysis also showed that two strains namely P. mendocina strain S5.2 and P. putida strain S13.1.2 were highly capable of tolerating other heavy metals including nickel, cobalt, cadmium, zinc and arsenic. Subsequently, complete genome analysis was conducted using Single Molecule, Real Time (SMRT) sequencing followed by genome assembly and annotation procedures to elucidate the genetic determinants involved in metal resistance of these strains. Methylome study in terms of genome-wide methylation patterns and presence of DNA methyltransferases in both strains were also conducted. Genome assembly has resulted in complete genome of P. mendocina strain S5.2 consisted in a 5.1 Mb circular chromosome with one linear plasmid, pPME5, at the size of approximately 250 kb. The linearity of this large plasmid was further verified using S1 nuclease treatment followed by pulse field gel electrophoresis. Besides, the complete iv genome of P. putida strain S13.1.2 comprised of one circular chromosome at the size of 6.6 Mb. A series of operons and gene clusters such as cop, cus, czc, nik, and asc systems were present, reflecting the observed metal resistance phenotypes. The features in terms of specificity and arrangements of these genetic determinants were also highlighted in the study. Methylome analysis revealed the presence of Type I and Type II DNA methyltransferases recognizing CGCANNNNNNGGG and GACGAG motifs, respectively in P. mendocina strain S5.2. For P. putida strain S13.1.2, one type II DNA methyltransferase recognizing GTTCCG motifs were also identified. Further analysis also showed that these genes were methylated indicating the possibility that these genes were regulated by DNA methylation. In addition, unique traits of P. mendocina strain S5.2 such as twitching motility and DNA methylation contributed by the presence of plasmid pPME5 were lost following plasmid curing of the strain. Such observations have demonstrated probable roles of the plasmid for fitness of the strain in native vineyard soil environments. In conclusion, the comprehensive genomic and phenotypic profiling of heavy metal resistance and methylome analysis have demonstrated the adaptation of Pseudomonas strains to the grapevine soils enriched with copper and perhaps other metals.